Qualitative study of morals in students' daily lives - Nurfauzia, Siti; Narada, Zaqiya; Khodijah, Siti; Nurajizah, Siti; Suty Gunawan, Dhinda Auliya (At-Tajdid: Jurnal Ilmu Tarbiyah, 2024)
This study aims to identify and understand moral issues among students and find effective solutions to improve their moral and ethical quality. The method used is descriptive qualitative, combining literature research. Data were collected through questionnaires and direct observation of students. The research findings show that morals significantly influence students' social and academic relationships on campus. The majority of respondents stated that good morals, such as respecting others' opinions, being honest, and being helpful, help build harmonious relationships with friends and lecturers. However, there are differences in the application of morals based on cultural or religious backgrounds. Challenges faced include situations where kindness is not reciprocated or emotions must be controlled. Nevertheless, respondents showed a commitment to consistently implementing positive moral values with support from peers and self-reflection. The role of family and the surrounding environment is recognized as important in shaping student morals. Programs and activities on campus, such as ethics seminars, social activities, and student organizations, help increase moral awareness. To enhance the application of morals, it is suggested to integrate moral education into the curriculum, organize seminars and workshops, and provide positive examples through lecturers and campus staff.